Ankle Arthritis. Issue 3 (16th July 2019) - Le, Vu; Veljkovic, Andrea; Salat, Peter; Wing, Kevin; Penner, Murray; Younger, Alastair
Ankle arthritis is a major source of morbidity impacting a younger working age population than hip and knee arthritis. Unlike the hip and knee, more than 70% of ankle arthritis cases are post-traumatic, with the remainder being inflammatory or primary arthritis. Nonoperative treatment begins with lifestyle and shoe-wear modifications and progresses to bracing, physical therapy, anti-inflammatory medications, and intra-articular injections. Ankle arthrodesis and total ankle arthroplasty are the 2 main surgical options for end-stage ankle arthritis, with debridement, realignment osteotomy, and distraction arthroplasty being appropriate for limited indications. Level of Evidence: Level V, expert opinion.